2020
DOI: 10.1002/cpt.1797
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Orally Administered Dronabinol on Optic Nerve Head Blood Flow in Healthy Subjects—A Randomized Clinical Trial

Abstract: It has been hypothesized that besides its intraocular pressure (IOP) lowering potential, tetrahydrocannabinol (THC) may also improve ocular hemodynamics. The aim of the present study was to investigate whether single oral administration of dronabinol, a synthetic THC, alters optic nerve head blood flow (ONHBF) and its regulation in healthy subjects. The study was carried out in a randomized, placebo‐controlled, double‐masked, two‐way crossover design in 24 healthy subjects. For each study participant, 2 study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 39 publications
(48 reference statements)
2
9
0
Order By: Relevance
“…Furthermore, no psychoactive effects, effects on IOP, or systemic hemodynamics were observed at the selected dose as reported previously. 16 This indicates that exogenous administration of a cannabinoid receptor agonist exerts vasoactive properties at the level of the retina and increases RBF in healthy subjects without altering OPP.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, no psychoactive effects, effects on IOP, or systemic hemodynamics were observed at the selected dose as reported previously. 16 This indicates that exogenous administration of a cannabinoid receptor agonist exerts vasoactive properties at the level of the retina and increases RBF in healthy subjects without altering OPP.…”
Section: Discussionmentioning
confidence: 99%
“…The screening examinations, inclusion/exclusion criteria, and study design have been published in a previous report and are only shortly summarized here. 16 In the 4 weeks before the first study day, a screening examination was performed, which included medical history survey; pregnancy test in women of childbearing potential; urine drug test and analysis; alcohol breath test; physical examination, including 12-lead ECG and measurement of systemic hemodynamics, blood draw for hematological status, clinical chemistry, and Hepatitis B, C, and HIV-Serology; a psychiatric examination using the modified Structured Clinical Interview (SCID-1) 19,20 test; and a routine ophthalmic examination comprising of assessment of best-corrected visual acuity, slit lamp biomicroscopy, indirect funduscopy, and measurement of IOP.…”
Section: Subjectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another interesting aspect of cannabinoid usage in glaucoma is connected with the neuroprotective capabilities of these molecules. To date, there are few studies assessing neuroprotective effects of cannabinoids in humans in term of functional or structural changes, but many studies demonstrated better outcomes for retinal ganglion cell (RGC) after different types of injuries in animals ( Table 1 ) [ 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ].…”
Section: Introductionmentioning
confidence: 99%
“…Endogenous cannabinoids may inhibit Endothelin-1 and consequently could play a neuroprotective role thanks to a better optic nerve head blood supply [ 14 ]. Oral THC indeed demonstrated to increase retinal perfusion and optic nerve head blood flow even at low dosages [ 43 , 44 ]. THC may therefore represent a promising therapeutic strategy since the optic nerve’s hypoperfusion has been identified as an important risk factor for glaucoma development and progression [ 52 ].…”
Section: Introductionmentioning
confidence: 99%